THE CORRELATION BETWEEN STUDENTS MOTIVATION AND THEIR ACHIEVEMENT SCORE IN ENGLISH LEARNING - Nickqietta Shareen Claudia Issabell; Iskandar Zulkarnain; Syfrina Prihatini (EXCELLENCE: Journal of English and English Education, 2021)
This journal discussed the correlation between students’ motivation and their achievement score in English learning for grade VIII students at SMP Teladan Sei Rampah. This study was conducted by using descriptive quantitative research design. The instrument for the data collection was questioner. The population of this study was 20 students. The result of data processing the correlation coefficient number was 0.723 and it was included in the strong category. Thus, it can be concluded that there was a correlation between students’ motivation and learning outcome in English grammar of the grade VIII students and this correlation was positive.